Determinants of Financial Distress: Stem from Profitability and Solvency Tribulations - Sunil Kumar, K.K; Renjith Mohan, P (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Profitability and solvency tribulations can directly lead to financial distress, which occurs when a company struggles to meet its financial obligations. Financial distress is a situation where a company is not able to meet or face difficulty to pay off its financial obligations. According to RBI’s definition negative working capital, cash loss and negative networth are the factors influencing Distresses. There are lots of causes of corporate failure which includes Profitability, Liquidity and solvency complications. Bankruptcy prediction models are among the techniques and tools for predicting future status of companies which can estimate the bankruptcy probability by compounding a set of financial ratios. This research paper has attempted to device models for predicting probability and solvency of financial distresses among the PSUs working under the Engineering sector in Kerala. In order to evaluate the ratios that can influence group status and quantify their connection, Multiple Logistic Regression analysis tool is administered. The main uses of logistic regression are that prediction of group membership and provide knowledge of the relationships and strength among the variables.